Testing system analysis as form of monitoring on course “Computer informational technologies” (on base of Distant Learning System “Kherson Virtual University ”) - Patsukova Г.В.; Gnyedkova О.О. (Journal of Information Technologies in Education (ITE), 2007)
In the article the usage of computer testing technologies for current and final examinations in the course “Computer information technologies ” for students of 1st course is considered.